Relationship Marketing Strategies in Building Long-Term Partnerships Between Contractor And Clients in the Property Sector - Pindia Maharani, Ni Putu; Elik Astari, Anak Agung; Ari Sudiartini, Ni Wayan (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
This study aims to analyze the influence of five dimensions of relationship marketing—communication, trust, commitment, empathy, and long-term orientation—on long-term partnerships between contractor companies and clients in the property sector, particularly in Tabanan, Bali. A quantitative method was applied using purposive sampling with 100 respondents. Data were analyzed using multiple linear regression with SPSS.